Two heads are less bubbly than one: team decision-making in an experimental asset market - Stephen L. Cheung; Stefan Palan (Institute for the Study of Labor (IZA), 2009)
We study the effect of team decision-making on bubbles and crashes in experimental asset markets of the kind introduced by Smith, Suchanek and Williams (1988). We find that populating such markets with teams of size two instead of individuals significantly reduces the severity of mispricing. In particular we observe that under our teams treatment, deviations in prices away from intrinsic value are significantly smaller in magnitude, shorter in duration and associated with lower volume and price volatility. We also find an unexpected gender effect in team composition, manifesting itself in more extreme - though not consistently more profitable - behaviour by all-male teams. Since these effects are not observed among male participants generally, we conjecture that they may be due to factors specific to the psychology of decision-making in male-dominated environments.
urn:nbn:de:101:1-200911041011
Keywords: C92; D70; G12; 330; Asset market experiments; price bubbles; group decision-making; gender composition of teams; Börsenspiel; Bubbles; Börsenkrise; Anlageverhalten; Gruppenentscheidung; Geschlecht